Evidence of the relative age effect in football in Australia - van den Honert, R. (Journal of Sports Sciences, 2012)
The birth date distributions of elite male and female footballers in Australia, from junior youth (age 14 and upwards) to senior (professional) players, were examined. A statistically significant relative age effect was found among junior male players, reducing in effect with increasing age. An inter-year relative age effect that became apparent among the players at national level in the Under-17 and Under-20 age groups, due to the timing of the respective World Cups for those age groups, was also identified. It is conjectured that this might lead to players born in certain years having a curtailed pathway in the elite game, leading to drop-out among this very elite group. In the case of women elite players, no significant relative age effect was found among youth players, possibly due to less fierce competition for places, although a significant effect was found to exist at senior elite level.